2008
DOI: 10.1093/jn/138.3.581
|View full text |Cite
|
Sign up to set email alerts
|

Zinc, Gravida, Infection, and Iron, but Not Vitamin B-12 or Folate Status, Predict Hemoglobin during Pregnancy in Southern Ethiopia

Abstract: The etiology of anemia during pregnancy in rural Southern Ethiopia is uncertain. Intakes of animal-source foods are low and infections and bacterial overgrowth probably coexist. We therefore measured the dietary intakes of a convenience sample of Sidama women in late pregnancy who consumed either maize (n = 68) or fermented enset (Enset ventricosum) (n = 31) as their major energy source. Blood samples were analyzed for a complete blood count, vitamin B-12 and folate status, plasma ferritin, retinol, zinc, albu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
135
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(153 citation statements)
references
References 35 publications
14
135
4
Order By: Relevance
“…The result of the present study was relatively similar with study conducted in Southern Ethiopia 53 % [12] and Nepal 61 % [20]. However, relatively lower than other reports from Ethiopia; prevalence of ZD was 76 % [30], 74 % [15] and 72 % [14] in Sidama and 66.7 % [13] in Gondar. It was also relatively lower than study from other countries, Kenya 66.9 % [16], Cameroon 82 % [18], and India 73.5 % [31].…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…The result of the present study was relatively similar with study conducted in Southern Ethiopia 53 % [12] and Nepal 61 % [20]. However, relatively lower than other reports from Ethiopia; prevalence of ZD was 76 % [30], 74 % [15] and 72 % [14] in Sidama and 66.7 % [13] in Gondar. It was also relatively lower than study from other countries, Kenya 66.9 % [16], Cameroon 82 % [18], and India 73.5 % [31].…”
Section: Discussionsupporting
confidence: 85%
“…About 73 (34.9 %) of the subjects had both deficiencies. A previous studies also found significant positive association between zinc deficiency and anemia [12,15,32,46]. As the studies are cross-sectional it is not viable to implicate causal inference.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Diets of rural Ethiopian populations are predominantly plant based with low intakes of animal-source foods (7) . Researchers have recognized the presence of mild to moderate IDA in lactating (8) and pregnant (9) women, as well as other women of reproductive age (10)(11)(12) , from Ethiopia. Recent studies have shown a high dietary intake of Fe by pregnant women (13) and young children (14) .…”
mentioning
confidence: 99%